Familial Clustering of Factor VIII and von Willebrand Factor Levels - Kamphuisen, Pieter W.; Houwing-Duistermaat, Jeanine J.; van Houwelingen, Hans C.; Eikenboom, Jeroen C. J.; Bertina, Rogier M.; Rosendaal, Frits R. (Thrombosis and Haemostasis, 1998)
Recently, we found that high levels of clotting factor VIII (>150 IU/dl) are common and make an important contribution to thrombotic risk. The determinants of high factor VIII:C are unclear and might be partly genetic. Therefore, we tested the influence of age, blood group and von Willebrand factor (VWF) levels on factor VIII:C levels, and investigated whether factor VIII:C levels are genetically determined. We performed an analysis of 564 female relatives of hemophilia A patients, who had visited our center for genetic counseling. In univariate analysis, AB0 blood group, age and VWF antigen (VWF:Ag) levels all influenced factor VIII:C levels. After adjustment for the effect of VWF:Ag levels, both blood group and age still had an effect on factor VIII:C levels. In sister pairs, the Pearson correlation coefficient between factor VIII:C levels was 0.17 (p = 0.024) and this correlation remained positive (0.15, p = 0.046) after correction for the influence of VWF:Ag. In mother-daughter pairs, no correlation of factor VIII:C levels was found. The correlation of VWF:Ag levels in sisterpairs was 0.41 (p <0.001) and in mother-daughter pairs 0.44 (p <0.001), in line with the assumption that VWF:Ag levels are under control of autosomal genes. Familial influence on plasma factor VIII:C and VWF:Ag levels was investigated with a recently developed familial aggregation test. This test verifies whether familial aggregation of a particular parameter exists in a set of pedigrees. In 435 women from 168 families, factor VIII:C as well as VWF:Ag levels correlated significantly within families, which suggests a familial influence. The familial aggregation was more prominent for VWF:Ag levels than for factor VIII:C levels, possibly because the genetic effect on VWF:Ag levels is larger than on factor VIII:C levels. Our results support the presence of a familial influence on factor VIII:C as well as on VWF:Ag levels.Our results support the presence of a familial influence on factor VIII:C as well as on VWF:Ag levels.